Development of a core subset of Chilean lowland subtropical and temperate maize (Zea mays L.) populations using near infrared transmittance - Campbell, M.R.=700 1 Anih, E.; Conatser, C.; Grau Saavedra, B.; Pollak, L.M.
(En, Fr, Es)
Ilus., 14 ref.
Keywords: ZEA MAYS; GERMOPLASMA; VARIACION GENETICA; ESPECTROSCOPIA INFRARROJA; ITALIA